Value dividends, the Harsanyi set and extensions, and the proportional Harsanyi solution - Manfred Besner (International Journal of Game Theory, 2020)
A new concept for TU-values, called value dividends, is introduced. Similar to Harsanyi dividends, value dividends are defined recursively and provide new characterizations of values from the Harsanyi set. In addition, we generalize the Harsanyi set where each of the TU-values from this set is defined by the distribution of the Harsanyi dividends via sharing function systems and give an axiomatic characterization. As a TU value from the generalized Harsanyi set, we present the proportional Harsanyi solution, a new proportional solution concept. A new characterization of the Shapley value is proposed as a side effect. None of our characterizations uses additivity.
Keywords: 330; TU-game; Value dividends; (Generalized) Harsanyi set; Weighted Shapley values; (Proportional) Harsanyi solution; Sharing function systems